Clarifying the Differences between Training, Development, and Enrichment: The Role of Institutional Belief Constructs in Creating the Purpose of Faculty Learning Initiatives. (14th March 2013) - Stabile, Christopher; Ritchie, William F.
Abstract: Many training issues arise as a matter of course at colleges and universities that are intended to bring greater efficiencies and compliance with preestablished operational guidelines. While vital, these issues are distinctively different from the issues surrounding professional development of the faculty. This chapter addresses those differences.